Measuring Speaking Gains from Hello Talk Use in Eleventh Grade: Quasi‑Experimental Evidence - Ardhita Chairunnisa; Husnaini Husnaini; Darmawan Budiyanto; Heru Setiawan (Media Akademika Publisher, 2026)
The objective of this study was to evaluate the effectiveness of the HelloTalk application in improving the speaking proficiency of eleventh-grade students at SMA Negeri 4 Palembang. A quantitative quasi-experimental design was employed, involving 120 students selected through purposive sampling and divided into experimental and control groups. The study used a pretest-posttest design to measure fluency, accuracy, grammar, mechanics, and pronunciation during an eight-week intervention with HelloTalk. The instrument’s content validity was confirmed using expert judgment and Aiken’s V formula, while data analysis was conducted through SPSS 24. The Kolmogorov-Smirnov test confirmed normal data distribution (p > 0.05). An independent sample t-test revealed a statistically significant difference in speaking performance between students taught using HelloTalk and those without, with a p-value of 0.000 (< 0.05). The findings indicate that HelloTalk substantially enhanced students’ speaking proficiency, particularly in fluency and self-expression, after consistent use over eight weeks. These results highlight the application’s positive impact on EFL learning and align with recent research promoting mobile and AI-assisted tools for language development. Thus, HelloTalk proves to be an effective platform to support formal classroom instruction in improving students’ English-speaking skills.